Microbiological and Physicochemical Properties of Beef Patties Added with Senduduk (Melastoma malabathricum L.) Leaf Powder at Different Levels: Sifat Mikrobiologi dan Fisikokimia Beef Patty yang Ditambahkan Bubuk Daun Senduduk (Melastoma malabathricum) dengan Level yang Berbeda - Suharyanto, Suharyanto; Sagala, Viona Apriyanti; Soetrisno, Edi; Warnoto, Warnoto; Hajrawati, Hajrawati (Buletin Peternakan Tropis, 2024)
This study investigates the effect of adding different concentrations of senduduk (Melastoma malabathricum L.) leaf powder (SLP) on the microbiological and physicochemical properties of beef patties. Senduduk leaf is known for its antimicrobial and antioxidant activities, which may help improve the shelf life and quality of meat products. Beef patties were prepared with varying levels of SLP (0%, 0.5%, 0.75%, and 1%) and evaluated at 0 and 5 hours of storage for total plate count (TPC), moisture content, water holding capacity (WHC), and pH. The results showed that the addition of SLP did not significantly affect the TPC or WHC at both time points. However, the moisture content of the patties with 0.75% SLP was significantly higher at 0 hours, while no significant differences were observed after 5 hours of storage. Similarly, the pH values remained stable across all treatments. These findings suggest that while SLP can initially influence moisture retention, its antimicrobial and physicochemical effects are limited, particularly after cooking, which likely degrades the bioactive compounds. Future research should explore the use of SLP in low-temperature cooking or cold storage to maximize its potential as a natural preservative.